2016
DOI: 10.1186/s40064-015-1653-8
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin-warfarin interaction in a mitral valve replacement patient receiving rifampin for infective endocarditis: a case report

Abstract: IntroductionWarfarin therapy is associated with many drug interactions that may cause a significant alteration in its anticoagulant effect. Rifampin is a widely used antimicrobial that has major interactions with several medications including warfarin due to its strong P-glycoprotein and liver enzyme inducer activity especially on CYP2C9, CYP3A4, CYP1A2 and CYP2C19.PresentationWe report a case of a 34-year-old Srilankan female chronically treated with warfarin for her mitral valve replacement. The patient deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 24 publications
(33 reference statements)
0
29
0
1
Order By: Relevance
“…Rifampin, a life-saving antimicrobial for tuberculosis, endocarditis, and meningitis, 14 is a clinically significant inducer of CYP2B6, CYP2C19, CYP2C8, CYP2C9, and CYP3A4, as well as P glycoprotein. 10 It induces CYP2C9 transcription by binding to its main De-novo synthesis regulatory nuclear receptor, pregnane X receptor ( PXR ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampin, a life-saving antimicrobial for tuberculosis, endocarditis, and meningitis, 14 is a clinically significant inducer of CYP2B6, CYP2C19, CYP2C8, CYP2C9, and CYP3A4, as well as P glycoprotein. 10 It induces CYP2C9 transcription by binding to its main De-novo synthesis regulatory nuclear receptor, pregnane X receptor ( PXR ).…”
Section: Introductionmentioning
confidence: 99%
“… 25–27 After the INR test was universally adopted, 28 several reports demonstrated that most patients who required the anti-infective along with anticoagulation were unable to maintain target INR. 14 , 29–36 …”
Section: Introductionmentioning
confidence: 99%
“…For example, rifampin interacts with warfarin resulted from its enzyme inducer activity on CYP2C9, CYP3A4, CYP1A2, and CYP2C19. There was a case report that a female on anticoagulation increased warfarin dose from 52.5 to 210 mg/week with a target INR during the 6-week treatment with rifampin for her infective endocarditis and she was stable on the warfarin dose of 80 mg/week 5 weeks after the end of rifampin therapy ( Fahmi et al, 2016 ). Multiple dose adjustment may occur when FA is combined with CYP1A2 or CYP3A4 substrates with a narrow therapeutic index.…”
Section: Discussionmentioning
confidence: 99%
“…However, LMWH have been proposed as a safe alternative, in case drug interactions are present, due to cytochrome p450 inhibition or induction, such in this case [24,25].…”
Section: Discussionmentioning
confidence: 99%